2014
DOI: 10.1155/2014/703291
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Cellulase Production by Penicillium funiculosum in a Stirred Tank Bioreactor Using Multivariate Response Surface Analysis

Abstract: Increasing interest in the production of second-generation ethanol necessitates the low-cost production of enzymes from the cellulolytic complex (endoglucanases, exoglucanases, and β-glucosidases), which act synergistically in cellulose breakdown. The present work aimed to optimise a bioprocess to produce these biocatalysts from the fungus Penicillium funiculosum ATCC11797. A statistical full factorial design (FFD) was employed to determine the optimal conditions for cellulase production. The optimal compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
1
4
2
Order By: Relevance
“…In current project several factors including time of incubation, agitation rate, aeration, oxygen transfer, pH and inoculum size were optimized for scale up studies by thermophillic T.dupontii. Similar study has been mentioned by Carvalho et al (2014) who reported cellulaes production in a stirred tank reactor by Penicillium sp.…”
Section: Optimization Of Different Factors For Enhanced Production Of...supporting
confidence: 87%
See 2 more Smart Citations
“…In current project several factors including time of incubation, agitation rate, aeration, oxygen transfer, pH and inoculum size were optimized for scale up studies by thermophillic T.dupontii. Similar study has been mentioned by Carvalho et al (2014) who reported cellulaes production in a stirred tank reactor by Penicillium sp.…”
Section: Optimization Of Different Factors For Enhanced Production Of...supporting
confidence: 87%
“…Besides this optimal enzyme activity also relies on the type or nature of microbial strain, their genetic makeup as well as its environmental and cultural conditions (Sudan & Bajaj, 2007). Besides this shorter fermentation time in case of mutant thermophilic T. dupontii as compared to other thermophilic indicates the stain possess the ability of economic enzyme production Carvalho et al (2014). The current findings are not in accordance with Carvalho et al (2014) who stated optimal cellulase production in the case of Penicillium at 72 hours.…”
Section: Optimization Of Different Factors For Enhanced Production Of...contrasting
confidence: 62%
See 1 more Smart Citation
“…For efficient hydrolysis of lignocellulosic biomass in to reducing sugars, enzyme preparation requires balanced activities of all the components of cellulases such as endo-β-1, 4-glucanases, exo-β-1, 4-glucanase, and β-glucosidase along with xylanases [11,13]. All these enzymes act synergistically to hydrolyze lignocellulosic biomass by the creation of new accessible sites for each other and prevention of product inhibition [14]. Products obtained after hydrolysis of lignocellulosic biomass are composed mainly of glucose, xylose, cellobiose, and oligosaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho and co-authors [33] carried out optimization of the culture media composition for strain P. funiculosum ATCC11797 in accordance with the full factorial (2 4 FFD) design. Th e se- [14,31].…”
mentioning
confidence: 99%